If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -3 = 2x Reorder the terms: -3 + 8y = 2x Solving -3 + 8y = 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8y = 3 + 2x Combine like terms: -3 + 3 = 0 0 + 8y = 3 + 2x 8y = 3 + 2x Divide each side by '8'. y = 0.375 + 0.25x Simplifying y = 0.375 + 0.25x
| y=-0.90(50)+128 | | -7y+2=8y+1 | | y=-0.90(40)+128 | | -31(4)= | | -17+(-26)= | | log[2](x)+log[2](x-3)=2 | | 12=3-1y | | a=p+4b+4c | | 10r^2+23rs+12s^2=10r^2+15rs+8rs+12s^2 | | y=-0.90(30)+128 | | X^2+28x-60=0 | | y=-0.90(20)+128 | | x+6=x(2) | | y+39=-41 | | y=0.90(20)+128 | | 9y^2-2=39 | | y+39=41 | | 9y-8x=-24 | | x^2=6x-x^2 | | I=500*0.14*2 | | 5.4x-2.5=25.1+10.2 | | 9x-y^2=0 | | x^2=4x-x^2 | | 3x=5.1 | | 5x^2+42x-27=0 | | -3(4s-1)-3=-3(8s+2)-5 | | 5x^2+42-27=0 | | -(8y+3)-(-7y-4)=1 | | (5n-2)(5n+2)=-24 | | y=0.60(35)+132 | | 16=-5t^2+20t+1 | | y=0.60(55)+132 |